Examining the Effect of Emotion to the Online Shopping Stores’ Service Recovery: A Meta-Analysis - Nguyen, Huan Minh; Minh, Hieu Le (Journal of Environmental Accounting and Management, 2026)
Based on attachment theory, this study aims to highlight the potential impact of customer’s emotional attachment in the context of online stores’ service recovery. Analyses of the data onto China, the findings indicate that once consumers have the emotional bond with a brand, the effect is much stronger than trust and service recovery fairness. It provides an insight to that online marketer should focus on the emotional attachment building and draw up the marketing strategy based on the connection, affection, passion, to create mutual memories for establishing the bond of emotion between online shopping stores and consumers.